WAYS TO IMPROVE THE RESULTS OF TREATMENT OF SEVERE COMBINED PELVIC INJURIES IN MODERN CONDITIONS - Burluka, Volodimir; Dorosh, Viktor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. To analyze the treatment of victims with severe combined pelvic trauma in the conditions of the existing trauma care system in Ukraine and to identify ways to improve the results of treatment of such injuries. Methods. The work was based on a study of the results of treatment of 406 victims with unstable pelvic injuries in polytrauma (UPIP) (ISS ≥ 17 points). Of these, 249 (61.3 % ) patients died in different periods of traumatic illness (TI). Two clinical groups were formed: the first — 137 (33.7 % ) patients, in whom differential surgical treatment tactics were performed based on the developed scales for assessing the severity of injury, the prognosis of the course of TI depending on its periods, as well as the proposed modern methods of diagnosis and surgical treatment of injuries of the pelvis and other anatomical areas, the second — 269 (66.3 %) patients, in whom generally accepted surgical treatment tactics were used. Results. Active surgical tactics using a differential approach allowed to increase the number of internal (combined) metal osteosynthesis in this category of victims from 40.4 to 72.1 %, to reduce the proportion of conservative treatment from 53.7 to 30.6%, and the active implementation of an improved protocol scheme for surgical treatment of victims with NUTP during hospitalization allowed to reduce mortality in the acute period of TC (up to 48 hours) from 77.7 to 63.9 %, p < 0.05, overall mortality from 69.9 to 44.5% (p < 0.01). Conclusions. The timing of delivery of a victim with a severe combined pelvic injury to a specialized trauma department is crucial at the prehospital stage of saving the patient’s life. The tactics of surgical interventions for injuries of extrapelvic localization, unstable pelvic fractures, pelvic organ trauma in the acute period of TI should be based on urgent indications, aimed primarily at stopping intrapelvic bleeding, the possibility of conducting single-stage or sequential emergency external fixation of the pelvic ring.